Overcoming Linguistic and Cultural Barriers in English Language Learning: An Exploration of Culturally Responsive Pedagogy - Rinnah Mae Salgado; Princess Shaira Koike; Rizcelyn Maglasang; Joemar Minoza (The English Teacher, 2024)
This study investigated the implementation and effectiveness of CRP in English language learning at Cebu Technological University-Tuburan Campus, addressing linguistic and cultural barriers for learners and explored diverse subcultures, including respondents’ religion, family structure, socioeconomic status, and educational attainment. Employing a mixed-methods design, the research utilized surveys and pre-post-tests with thirty-three respondents, and interviews with six informants to gather data. Findings revealed a broad age range, a predominance of female participants, and a religiously influenced demographic. The pre-post-test results demonstrated a significant improvement in overall written communication competencies, highlighting a substantial improvement in the application of morphological concepts in writing essays, coupled with sustained high proficiency in grammar. A multiple regression analysis identifies the varying influences of demographic factors on test scores. Teachers perceived CRP as a catalyst for inclusive education, emphasizing customized approaches aligned with cultural backgrounds. Thus, CRP positively impacts language learning outcomes in diverse educational settings. Overcoming Linguistic and Cultural Barriers in English Language Learning: An Exploration of Culturally Responsive PedagogyRecommendations include implementing an action plan to enhance language proficiency and overcome linguistic and cultural barriers in English language learning. Findings contribute to a broader understanding of CRP’s significant application in a culturally diverse educational context.
Keywords: Culturally Responsive Pedagogy, linguistic and cultural barriers, English language learners, subcultures, written communication